2021
DOI: 10.1038/s41598-021-03555-7
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic deep brain stimulation modulates cycles of seizure risk in epilepsy

Abstract: Chronic brain recordings suggest that seizure risk is not uniform, but rather varies systematically relative to daily (circadian) and multiday (multidien) cycles. Here, one human and seven dogs with naturally occurring epilepsy had continuous intracranial EEG (median 298 days) using novel implantable sensing and stimulation devices. Two pet dogs and the human subject received concurrent thalamic deep brain stimulation (DBS) over multiple months. All subjects had circadian and multiday cycles in the rate of int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 64 publications
3
69
0
Order By: Relevance
“…Pioneering work from the early 20 th century identified circadian and multiday [8][9][10] periodicities in seizure occurrences based on meticulous clinical records and seizure diaries kept for individuals living in supervised care facilities. More recently, chronic intracranial recordings from clinical 4,[11][12][13][14] and investigational 1,2,5,6,15 devices have revealed that for many individuals with epilepsy interictal epileptiform activity (IEA) is modulated over circadian and multiday cycles, and that seizures occur at preferred phases of these underlying cycles. 3 By measuring seizure risk relative to physiological signals amenable to continuous temporal sampling (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering work from the early 20 th century identified circadian and multiday [8][9][10] periodicities in seizure occurrences based on meticulous clinical records and seizure diaries kept for individuals living in supervised care facilities. More recently, chronic intracranial recordings from clinical 4,[11][12][13][14] and investigational 1,2,5,6,15 devices have revealed that for many individuals with epilepsy interictal epileptiform activity (IEA) is modulated over circadian and multiday cycles, and that seizures occur at preferred phases of these underlying cycles. 3 By measuring seizure risk relative to physiological signals amenable to continuous temporal sampling (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest multiday cycles, including circaseptan 32 (weekly) and circamonthly 33 cycles, have been identified in the regulation of immune, 26 endocrine, 28,34 metabolic, 35 and cardiovascular 36,37 systems, in human behavior, 32 as well as in brain excitability 17,20 and seizure risk. [2][3][4][5][6]12 Prior work on naturally occurring human and canine epilepsy has established that multiday cycles are common, with evidence for grouplevel circa-weekly, bi/tri-weekly, and monthly cycles. 12 Wearable devices that provide multimodal recordings of body physiology are available to the lay population in popular commercial smartwatch systems, as digital health has become a growth area for the technology sector.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is now well-established that seizures and seizure risk show multidien rhythms ( 158 ) in humans ( 159 , 160 ) and canines ( 161 ). This important observation, that was first reported nearly 100 years ago ( 162 ), should prove useful for seizure forecasting and intelligent chronotherapy ( 64 , 120 ).…”
Section: Seizure Detection and Forecasting And Its Application In Neu...mentioning
confidence: 82%
“…Implantation and application of the described stimulation algorithm in the canine patient successfully prevented status epilepticus and reduced coherent cluster seizures during the follow-up phase of 7 months ( 64 ). Another closed-loop investigational device, sensing and stimulating both hippocampi and anterior nuclei of the thalamus, was implanted in two dogs with idiopathic epilepsy ( 120 , 121 ). The authors reported that the device tracked successfully seizure activity, but did not report about how successful the device was in suppressing epileptic seizures.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…In combination with the infrequent nature of seizures, where patients spend most of their time in a non-seizure state, physicians are thus required to optimize therapy over extended periods of time ( Bergey et al., 2015 ; Blachut et al., 2015 , 2017 ; Hoppe et al., 2007 ; Salanova et al., 2015 ). Access to newer sensing-enabled devices capable of chronic data recording are highlighting a clearer role of biological rhythms in epilepsy ( Baud et al., 2018 ; Gregg et al., 2020 , 2021 ; Karoly et al., 2021 ). More specifically, long-term intracranial EEG (iEEG) recordings from human and canine patients demonstrate electrophysiological biomarkers with circadian and infradian seizure periodicities that occur independent of medication dosing that are believed to reflect endogenous rhythms associated with seizure risk ( Baud et al., 2018 ; Gregg et al., 2020 ; Karoly et al., 2018 ), Figure 3 .…”
Section: Biological Rhythms and Neuromodulationmentioning
confidence: 99%